Une épidémie d’insectes, facteur de déboisement dans le Québec - Roy, Gilles (Cahiers de géographie du Québec, 1958)
Spruce budworm bas invaded the forest of Québec since 1939, especially the pines of the coniferous area. There are jour major infested regions : three are located on the North shore of the St. Lawrence river : in the Gatineau river bassin, in the Laurentians between the Lachute Area and lake St. John, and in the North Shore region behind Baie Comeau Sept-Iles. The fourth region starts behind Rimouski and spreads eastward, covering the whole Gaspé peninsula. In this last the authorities are quite concerned about this plague, which is becoming a serious menace to the forest industries. Various air-spays have been used during the past jour years in order to circumscribe the dammages, and more than 4,000,000 acres have been treated with DDT, first step toward the rehabilitation of the forest.